IMPLEMENTASI KOMPETENSI PEDAGOGI GURU SEKOLAH DASAR - harianingsih - (Universitas Muhammadiyah Kuningan, 2023)
This study aims to describe the pedagogic competence of 10 teachers at Patemon 02’s Elementary School Gunungpati Semarang Central Java Indonesia. The method used is descriptive quantitative with an instrument consisting of 50 question items and 7 indicators. The results showed that the ability of teachers to understand the characteristics of students was 81.3%, the ability to master the theory and principles of learning that educates 80.52%, the ability to develop curriculum 81.33%, the ability to carry out learning 81.48%, the ability to utilize information and communication technology 75.15%, the ability to facilitate the development and actualization of the potential of students 80.65%, the ability to conduct evaluations and assessments of learning outcomes 80.56%. So it can be concluded that the pedagogic ability of the teachers of Patemon 02’s Elementary School is at a good level.